(untitled) (Olhares, 2019)
This article argues about the nature of academic research in the field of arts, especially considering the hierarchical notion that sets a higher value to orthodox models of research in detriment of research expressed in the artistic creation act itself. Parallels are drawn between research in the field of arts and research in the field of neuroscience, considering the work of Oliver Sacks and terms of comparison established by Michel Foucault in The order of the discourse (1970).